1999
DOI: 10.1515/cclm.1999.060
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction by Traditional and New Markers of Inflammation in Patients with Sepsis

Abstract: Patients (n=242) admitted to intensive care unit for longer than 48 hours were categorised for sepsis according to American College of Chest Physicians/Society of Critical Care Medicine (ACCP/SCCM) Consensus Conference criteria. Body temperature, leukocyte count, C-reactive protein (CRP) and procalcitonin (PCT) as well as tumor necrosis factor-alpha (TNF-alpha), interleukin (IL)-6, IL-8, IL-10 and HLA-DR expression on monocytes were determined. Data of one randomly chosen day per patient entered analysis. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
22

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 42 publications
7
66
0
22
Order By: Relevance
“…Although PCT-guided antibiotic therapy is associated with a reduction in antibiotic usage and may reduce overall costs of care, an increase in hospital mortality of 7% under PCT guided conditions could not be ruled out by a meta analysis of Heyland et al [33] . Despite the association of high PCT and CRP levels in the onset of sepsis with poor outcome [34,35] , the prognostic value of PCT is limited [10] .…”
Section: Crp and Pctmentioning
confidence: 99%
“…Although PCT-guided antibiotic therapy is associated with a reduction in antibiotic usage and may reduce overall costs of care, an increase in hospital mortality of 7% under PCT guided conditions could not be ruled out by a meta analysis of Heyland et al [33] . Despite the association of high PCT and CRP levels in the onset of sepsis with poor outcome [34,35] , the prognostic value of PCT is limited [10] .…”
Section: Crp and Pctmentioning
confidence: 99%
“…1- 5 The increase of PCT concentrations in patients with sepsis correlates with mortality. 6 Experimental data have shown that PCT plays an important role during monocyte adhesion and migration, and further has a stimulatory effect on inducible nitric oxide synthase gene expression in patients with sepsis, representing key features of the atherosclerotic process. 7-9 Whereas an increasing number of studies have investigated the potential use of PCT in other infectious diseases such as pneumonia, bacterial meningitis and malaria, 10-12 only a few studies have been done on the impact of PCT on cardiovascular prognosis in patients with coronary artery disease (CAD).…”
Section: Rocalcitonin (Pct) Is a Well-established Biomarkermentioning
confidence: 99%
“…К настоящему времени доказана корреляция уровня ПКТ с тяжестью синдрома полиорганной недостаточности [12]. В многочисленных исследованиях, преимущественно включавших пациен-тов с сепсисом, находившихся в отделении интенсивной терапии, продемонстрировали значительно более высо-кую прогностическую ценность повышения содержания ПКТ в отношении ТБИ в сравнении с концентрацией СРБ и числом лейкоцитов [13,14]. Интересно, что такого же повышения ПКТ в сыворотке крови почти не происходит при вирусных инфекциях, что, вероятно, связано с инги-бирующим действием интерферона ␥ на процессы выра-ботки ПКТ [15].…”
Section: маркеры воспаленияunclassified